Sustainable Geotrail Planning and Geosite Risk Assessment in Purwodadi Village, Indonesia: A Geoheritage Perspective - I Ketut Ari Pegatariana; Adi Susilo; Faridha Aprilia; Ida Bagus Oka Agastya (Yayasan Ghalih Pelopor Pendidikan, 2025)
Purwodadi Village, located in East Java, Indonesia, has recently gained recognition as one of the top tourism villages in the country. With its rich geological heritage and unique landforms, the area holds significant potential for geotourism development. This study explores sustainable geotrail planning by characterizing geodiversity across nine identified geosites and assessing their vulnerability to degradation. Field surveys and geosite inventories were conducted following the Geological Agency’s technical standards, supported by a 4A analysis framework consisting of attraction, accessibility, amenities, and ancillary services. Additionally, a weighted overlay method incorporating slope, rainfall, soil type, and land cover data was used to map degradation risk. The findings reveal that each geosite possesses moderate to high geological significance, with varying degrees of susceptibility to erosion and anthropogenic impact. The proposed geotrails are thematically organized to reflect the area's ancient volcanic history, offering both educational and recreational value. The results contribute to sustainable tourism planning and geoheritage conservation efforts by identifying strategies to manage geosites while preserving their scientific and aesthetic value for future generations.